The Effectiveness of Three Strains of Beauveria bassiana (Balsamo) Vuillemin Isolate with Different Densities and Tobacco Leaf Extract on Plutella xylostella Linnaeus (Lepidoptera: Plutellidae) - Hadi, Mochammad Syamsul; Siringoringo, Intan; Widjayanti, Tita; Setiawan, Yogo (Plantropica: Journal of Agricultural Science, 2023)
This study aims to determine the pathogenicity and feeding inhibition of three B. bassiana isolate strains with different densities and concentrations of EDT (Tobacco Leaf Extract) in controlling P. xylostella. Research conducted in the Lab. Brenjonk Biological Agency and Lab. BPTPH Pasuruan from October to December 2022. This study used a Randomized Block Design (RAK) to examine the mortality and feeding inhibition of B. basiana and EDT strain isolates against P. xylostella. And probit analysis to find out the LC50 value and LT50 value. In this study, there were 17 treatments consisting of 15 larvae in each treatment and 4 repetitions were carried out. The results showed that the highest mortality percentage of P. xylostella was found in B. bassiana isolates of Bojonegoro and Jatisari strains at densities of B. bassiana 108 and 1010. The lowest LC50 value of B. bassiana isolates was the Bojonegoro strain and the EDT LC50 value was 43.79 ml/lt. Meanwhile, the lowest LT50 value was found in the EDT treatment at 28.40 hours. Based on the test results, it was also known that B. bassiana and EDT had potent feeding inhibition against P. xylostella. However, the use of EDT in controlling P. xylostella was less effective and efficient than the application of B. bassiana.